Central venous catheter-associated bloodstream infection in the Intensive Care Unit (Research, Society and Development, 2023)
Objective: The general objective of this work is to understand ways of preventing bloodstream infection associated with central venous catheters, and as a specific objective to understand how it occurs in the ICU, to know the causes, to identify the main etiological agents related to this type of infection. , to investigate the use of central venous catheter and main associated infections, and to contribute to the scientific community in research related to the subject. Method: This is an integrative literature review, where searches were carried out in the following databases: Lilacs (Latin American and Caribbean Literature in Health Sciences), Medline (National Library of Medicine) and Scielo (Scientific Electronic Library Online). Articles were selected by year, language, studies in full and that addressed the issue of bloodstream infection associated with central venous catheter. Results: The study showed that health professionals do not have much knowledge about dunbles and do not adequately prevent infections, it also showed that hand washing is not carried out properly and efficiently. Conclusion: It is necessary that institutions seek to provide knowledge about prevention and education protocols on an ongoing basis and that professionals seek to perform dunbles and hand hygiene so that this prevention is carried out effectively, thus avoiding bloodstream infections. associated with central venous catheter.